Digestion of certain fractions of dietary fiber in humans - Holloway, W D; Tasman-Jones, C; Lee, S P (The American journal of clinical nutrition, 1978)
The digestion of cellulose, hemicellulose, and lignin has been investigated in humans. Two groups of subjects were studied--healthy subjects with an ileostomy and normal subjects. Both were put on a fixed diet of known cellulose, hemicellulose, and lignin content. From the feces excreted the fiber components were measured by the acid and neutral detergent method. From the small bowel 84.5% of the ingested cellulose was excreted from the ileostomy subjects. From the normal subjects 22.4% of the ingested cellulose was excreted, indicating approximately 80% of the cellulose was digested in the normal subjects. From the water insoluble ingested hemicelluloses 27.5% were excreted from the small bowel, 4.0% from normal subjects. That is approximately 96% digestion of the hemicelluloses in normal subjects. Lignin was found to be undigested in both the small and large bowel. This has important implications in future fiber research.